Hubungan Perilaku Penggunaan Gadget Dengan Miopia Pada Anak Usia Sekolah Di SDN Sukaraja 2 - Firdawati Juvitha, Resta (Jurnal Keperawatan Muhammadiyah, 2024)
Myopia is a refractive disorder that occurs when the light beam that enters the eye parallel to the optical axis becomes focused in front of the retina when the eye accommodation is relaxed. It is estimated that by 2050, about 49.8% of the world's population will have myopia and 9.8% will have high myopia. The introduction of gadgets in school-age children is still too early where children would prefer to be physically active or play live in groups rather than familiar with gadgets. The aim of this study is to find out the relationship between the behavioural use of gadgets and myopia in school-age children in SDN Sukaraja 2. The research method used is quantitative with research survey design correlation and cross-sectional approach. This research instrument uses a questionnaire and a Snellen chart contained in the SDIDTK landing book issued by Kemenkes. (2016). Research sample 43 5th grade students at SDN Sukaraja 2. Data analysis in the trial using a chi-square correlation test. The results of this study found no correlation between gadget use behavior and myopia in school-age children in SDN Sukaraja 2 (Asimp.Sig 0,077 > 0,05). It can be concluded that the behavior using the gadget is in the good category with the highest score is 29 (67.44%). Myopia in children is included in the normal with the most visual strength score is 37 (86.05%) and there is no significant relationship between the behaviour using the device and myopia.